Potasssium chloride as a nutrient seed primer to enhance salt‑tolerance in maize - Zaman, Badar -uz-; Ali, Arshad; Hyder, Syed Ishtiaq; Arshadullah, Muhammad; Bhatti, Saqib Umar (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine if KCl could be a useful nutrient primer for safe seed germination in maize crop under salt stress conditions. Seed priming was done using 50 mmol L-1 of muriate of potash, and germination and seedling growth were evaluated after salt stress with NaCl up to 50 mmol L-1. Another set of seeds was tested under the same salt stress conditions without priming. Under salinity stress, germination percentage, germination rate index, germination coefficient, and seedling vigor indexes were higher in primed seeds. In unprimed seeds, mean germination time increased, while the germination rate index and the fresh and dry matter mass decreased more sharply with salinity stress. The Na/K ratio was higher in unprimed seeds.